2014
DOI: 10.1111/rda.12419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Post‐Thaw Addition of Seminal Plasma on Motility, Viability and Chromatin Integrity of Cryopreserved Donkey Jack (Equus asinus) Spermatozoa

Abstract: Pregnancy rates in donkeys after artificial insemination with cryopreserved semen are still low, compared to the horse species. Addition of autologous seminal plasma to frozen-thawed semen appeared to improve pregnancy rates. The aims of this study were to evaluate (1) sperm motility and plasma membrane integrity after thawing (T0) and after one and 2 h (T1 and T2) of post-thaw incubation in either 0% (SP0) or 70% (SP70) autologous seminal plasma and (2) sperm motility, plasma membrane integrity and DNA qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
1
13
2
Order By: Relevance
“…The average value of acrosome membrane integrity measured by fluorescence probes was lower than that reported in the literature for donkeys, an average of 44.5 % (Sabatini et al 2014). However, it is important to note that the average of alive sperm without acrosome reaction was similar to plasm membrane integrity.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…The average value of acrosome membrane integrity measured by fluorescence probes was lower than that reported in the literature for donkeys, an average of 44.5 % (Sabatini et al 2014). However, it is important to note that the average of alive sperm without acrosome reaction was similar to plasm membrane integrity.…”
Section: Discussioncontrasting
confidence: 57%
“…But the progressive motility values (PROGMOT); linearity (LIN); average path velocity (VAP); progressive linear velocity (VSL) and curvilinear velocity (VCL) were lower than those reported by Sabatini et al (2014) being 40.1± 8.8 % PROGMOT; 110.0 ± 7.2 VAP; 100.4 ± 6.3 VSL and 160.8 ±13 VCL (Table 2). …”
Section: Discussionmentioning
confidence: 70%
“…Thus, it is crucial to choose a suitable time scale for our study. Previous reports in donkeys [19] and horses [12] have shown that significant changes in sDF between treatments and individuals occurred from 6 to 24 h of incubation at 37 °C when using a chromatin dispersion test, or 4 h of incubation for the sperm chromatin structure assay (SCSA) by flow cytometry [20]. However, since one of the objectives of this study was to fine-tune a model, in order to adjust the model to reality, we needed to have as many points as possible.…”
Section: Discussionmentioning
confidence: 99%
“…llama [54] or pig [55], addition of seminal plasma to the thawed sperm before insemination seems to improve fertilisation rate. In donkeys, the addition of seminal plasma to post-thaw sperm showed no improvement in in vitro sperm characteristics [27] and, as shown in our study, had no effect on pregnancy rate, when it was added to the thawed sample before insemination. This is yet another demonstration of the fact that species are different from each other and thus require species-specific customisation of protocols.…”
Section: Discussionmentioning
confidence: 63%
“…While much has been done and written on cryopreservation of stallion semen, only a handful of studies could be found in the scientific literature on issues related to donkey semen cryopreservation. These includes reports on several donkey breeds such as the Baudet Du Poitou [1014], Zamorano-Leonés [15,16], Pêga [17–19], Martina Franca [20,21], Catalonian [13,22], Grand Noir du Berry [13], Andalusian [2325], Amiata [26,27], Abyssinian (Lemma et al, unpublished data), the American standard breed [28], and recently also for the onager [29,30]. Post-thaw sperm quality in these studies, as judged by laboratory evaluation techniques, was fair to excellent.…”
Section: Introductionmentioning
confidence: 99%